STRATEGI KOMUNIKASI MEDIA MASSA MENGEKSPLORASI PERAN GENERASI Z DAN MILENIAL DALAM MENDORONG PERTUMBUHAN EKONOMI HIJAU - Satyadinatha, I Nyoman Dhani; Purnama Yasa, Komang Widya; Dharma Yanti, I Wayan Alinda (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2025)
The green economy is a form of paradigm shift in society about the importance of a more environmentally friendly future, especially for generation Z and Millennials. Mass media has an influence in presenting information and shaping people's views, especially regarding the green economy. This research will examine how mass media communication strategies explore the role of generation z and millennials in encouraging green economic growth. This research uses a descriptive qualitative method with data collection techniques in the form of non-participant observation, semi-structured interviews, and documentation analysis. The research location is Mataram City Mass Media with a focus on Suara NTB, Lombok Post and Radar Lombok. Informant selection technique with purposive sampling. This research also uses the News Factory Model and Audience Reception Theory approaches. The results showed that newspapers are not the phase for Generation Z and Millennials so that the mass media in encouraging green economic growth news that follows the current generation's social media trends (Instagram, Tiktok, Youtube, Reel, and Podcast) so that it demands conventional mass media to be digital. The results of mass media coverage must be measured for effectiveness to determine the interest of news by this group. So that the challenges regarding the green economy for mass media to news viewers, especially young people, can be minimized through infrastructure.